Contextual Teaching Strategies in Arabic Language Education: Bridging Theory and Practice for Enhanced Learning Outcomes - Sitti Hasnah; Mohamad Idhan; Muh. Jabir (At-Ta'dib, 2024)
Abdul Hakim, Muhammad Kamal. “Improving Arabic Academic Writing Skills Through Contextual Teaching And Learning Approach.” ALSINATUNA 3, no. 2 (20 Agustus 2018): 183. https://doi.org/10.28918/alsinatuna.v3i2.1169. As’ad, Mahrus, Ahmad Bukhori Muslim, dan Imam Ghozali Budiharjo. “Qur’anic Perspective on Empowering Humanistic Foreign Language Teaching.” Al-Bayān – Journal of Qurʾān and Ḥadīth Studies 17, no. 2 (17 Desember 2019): 168–94. https://doi.org/10.1163/22321969-12340074. Badawi, Habib. “Learning from Japan: Advancing Education in the Arab and Islamic World through Creative Approaches.” Nazhruna: Jurnal Pendidikan Islam 6, no. 2 (18 Juni 2023): 290–305. https://doi.org/10.31538/nzh.v6i2.3516. Dajani, Basma Ahmad Sedki, Salwa Mubaideen, dan Fatima Mohammad Amin Omari. “Difficulties of Learning Arabic for Non-Native Speakers.” Procedia - Social and Behavioral Sciences 114 (Februari 2014): 919–26. https://doi.org/10.1016/j.sbspro.2013.12.808. Febriyanti, Ulfa, Maman Abdurrahman, dan Asep Sopian. “Is Historical Study of Nahwu on Madrasah Basra and Kufa Important to Teach? The Analysis of Opinion on Indonesian AFL Students.” Al-Ta’rib : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya 9, no. 1 (1 Juni 2021): 25–34. https://doi.org/10.23971/altarib.v9i1.2522. Haerazi, Haerazi, Zukhairatunniswah Prayati, dan Rully May Vikasari. “PRACTICING Contextual Teaching And Learning (Ctl) Approach To Improve Students Reading Comprehension In Relation To Motivation.” English Review: Journal of English Education 8, no. 1 (27 Desember 2019): 139. https://doi.org/10.25134/erjee.v8i1.2011. Hanyfah, Siti, Gilang Ryan Fernandes, dan Iwan Budiarso. “Penerapan Metode Kualitatif Deskriptif Untuk Aplikasi Pengolahan Data Pelanggan Pada Car Wash.” Semnas Ristek Seminar Nasional Riset Dan Inovasi Teknologi 6, no. 1 (2022): 339-44,. https://doi.org/10.30998/semnasristek.v6i1.5697. Hazuar, Hazuar. “Konsep I’rab Dalam Pandangan Ibrahim Musthafa dan Ibrahim Anis.” Arabiyatuna : Jurnal Bahasa Arab 3, no. 1 (14 Mei 2019): 163. https://doi.org/10.29240/jba.v3i1.796. Letmiros, Letmiros. “Arabic: Why Indonesians Have To Learn It?” International Review of Humanities Studies 4, no. 2 (30 Juli 2019). https://doi.org/10.7454/irhs.v4i2.166. Mahmudi, Ihwan, Neni Naqiyah, dan Alif Cahya Setiyadi. “The Influence Of High Order Thinking Skill (Hots) Based Questions On Arabic Language Learning Outcomes Of Madrasah Tsanawiyah Student.” At-Ta’dib 18, no. 2 (2023): 49–70. https://doi.org/10.21111/attadib.v18i2.10547. Majadly, Haifaa, dan Aharon Geva-Kleinberger. “Arabic Grammar Curricula for Primary Schools in Middle Eastern Countries: A Comparative Study.” Journal of Educational Media, Memory, and Society 12, no. 2 (1 September 2020): 1–29. https://doi.org/10.3167/jemms.2020.120201. Muid, Abdul, dan Firman Afrian Pratama. “Project-Based Learning Model in Improving Student’s Writing Skills in the Department of Arabic Language Education in Higher Education.” Studi Arab 15, no. 1 (30 Juni 2024): 1–8. https://doi.org/10.35891/sa.v15i1.4333. Sehri, Ahmad. “Metode Pengajaran Nahwu Dalam Pengajaran Bahasa Arab.” HUNAFA: Jurnal Studia Islamika 7, no. 1 (15 Juni 2010): 47. https://doi.org/10.24239/jsi.v7i1.108.47-60. Sugiyon, Sugiyono. Metode penelitian kuantitatif, kualitatif, dan R&D. 3 ed. Bandung, Indonesia: Alfabeta, 2021. Wahyudi, Hakmi, Hakmi Hidayat, dan Sri Wahyuni Hakim. “Pemikiran Gramatikal Bahasa Arab Oleh Linguistik Arab (Studi Tokoh Lintas Madzhab Nahwu).” Al-Fikra : Jurnal Ilmiah Keislaman 19, no. 1 (7 Agustus 2020). https://doi.org/10.24014/af.v19i1.10235. Yusuf, A. Muri. Metode Penelitian: Kuantitatif, dan Penelitian Gabungan. Edisi Pertama. Jakarta: Kencana, 2017. https://books.google.co.id/books?id=RnA-DwAAQBAJ&printsec=frontcover&hl=id#v=onepage&q&f=false.